(Dicyanamido)[tris(2-pyridylmethyl)amine]zinc(II) perchlorate - Li, Hong (International Union of Crystallography, 2008)
In the title complex, [Zn(C(2)N(3))(C(18)H(18)N(4))]ClO(4), the Zn(II) ion has a slightly distorted trigonal–bipyramidal ZnN(5) coordination geometry. The crystal structure is stabilized by weak intermolecular C—H⋯O and C—H⋯N hydrogen bonds. In addition, there are relatively close contacts between the O atoms of the perchlorate anion and symmetry-related pyridine rings [O⋯Cg = 3.179 (3) and 3.236 (3) Å, where Cg is the centroid of a pyridine ring], and between the terminal N atom of the dicyanamide ligand and pyridine rings [N⋯Cg = 3.381 (4)–3.761 (3) Å]. The central N atom of the dicyanamide ligand is disordered over two sites in an approximately 0.6:0.4 ratio.